Aggregation characteristics of protein during wheat flour maturation. (13th August 2018) - Wang, Na; Ma, Sen; Li, Li; Zheng, Xueling
Abstract: BACKGROUND: The protein aggregation characteristics of three types of freshly milled wheat flour with high, medium or low gluten were investigated during 90 days of maturation. Changes in the content and particle size of the glutenin macropolymer (GMP), contents of sulfhydryl groups and disulfide bonds (SS), and secondary structure and molecular weight distribution of the protein were determined. RESULTS: For high, medium and low gluten flour, GMP content increased to 22.25, 13.72 and 10.32 g kg −1 ; free sulfhydryl group content decreased by 5.5%, 4.1% and 4.4%; and SS content increased by 1.6%, 1.8% and 2%, respectively. The proportion of β ‐sheet and random coil increased, and the proportion of α ‐helix and β ‐turns decreased. The polymeric protein content increased, whereas that of gliadin decreased. CONCLUSION: Protein aggregation mediated by SS cross‐linking helped develop a stronger gluten network. The findings provide theoretical support for the changes in protein structure during flour maturation and also help to predict the quality of wheat flour and its products. © 2018 Society of Chemical Industry